2022
DOI: 10.3390/gels8030191
|View full text |Cite
|
Sign up to set email alerts
|

4,6-O-Phenylethylidene Acetal Protected D-Glucosamine Carbamate-Based Gelators and Their Applications for Multi-Component Gels

Abstract: The self-assembly of carbohydrate-based low molecular weight gelators has led to useful advanced soft materials. The interactions of the gelators with various cations and anions are important in creating novel molecular architectures and expanding the scope of the small molecular gelators. In this study, a series of thirteen new C-2 carbamates of the 4,6-O-phenylethylidene acetal-protected D-glucosamine derivatives has been synthesized and characterized. These compounds are rationally designed from a common su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The gelator 15 (when R′ = p -methoxyl benzyl) formed spontaneous gels when adding aqueous solutions of metal ions to the gelator solution dissolved in a small amount of DMSO. Wang's group also reported several C-2 N -linked carbamates of the 4,6- O -phenylethylidene acetal protected d -glucosamine derivatives 16 , 18 which were prepared by commercially available chloroformate and the previous literature-reported amine headgroup. 19 Among the synthesized carbamates, the isopropyl derivative ( 16 , R = iPr) is a hydrogelator and can form hydrogel at 0.2 wt%.…”
Section: Monosaccharide Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The gelator 15 (when R′ = p -methoxyl benzyl) formed spontaneous gels when adding aqueous solutions of metal ions to the gelator solution dissolved in a small amount of DMSO. Wang's group also reported several C-2 N -linked carbamates of the 4,6- O -phenylethylidene acetal protected d -glucosamine derivatives 16 , 18 which were prepared by commercially available chloroformate and the previous literature-reported amine headgroup. 19 Among the synthesized carbamates, the isopropyl derivative ( 16 , R = iPr) is a hydrogelator and can form hydrogel at 0.2 wt%.…”
Section: Monosaccharide Derivativesmentioning
confidence: 99%
“…Wang group also reported several C-2 N-linked carbamates of the 4,6-O-phenylethylidene acetal protected D-glucosamine derivatives 16, which was prepared by commercially available chloroformate and previous literature reported amine headgroup. 18 Among the synthesized carbamates, the isopropyl derivative (16, R = iPr) is a hydrogelator and can form hydrogel at 0.2 wt%. This hydrogelator gels with tetra alkyl ammonium salts to create effective gel electrolytes.…”
mentioning
confidence: 99%
“…Further, synthesis of C-2 carbamates of para -phenylethylidene acetal-protected d -glucosamine derivatives 124 was also reported along with their gelation properties. The study also reported isopropyl carbamate as a highly efficient hydrogelator, which also exhibited the ability to form gel electrolytes.…”
Section: New Carbohydrate-based Gelatorsmentioning
confidence: 99%
“…Since carbohydrates are biocompatible, biodegradable, rich in stereochemistry, nontoxic, eco-friendly, inexpensive, and moreover derived from abundant renewable resources, they have proven to be an ideal choice for the development of organogels compared with other gel types . Carbohydrate-derived organogelators display applications in various fields, such as oil-spill recovery, semiconducting fabrics, CO 2 absorption, generation of nanocomposite materials, soft-optical devices, separating biomolecules, lectin binding, controlled drug encapsulation, release and delivery, self-healing, metal ion detection, and many others. …”
Section: Introductionmentioning
confidence: 99%